Ventricular and lumbar cerebrospinal fluid concentrations of Alzheimer's disease biomarkers in patients with normal pressure hydrocephalus and posttraumatic hydrocephalus - Brandner, Sebastian; Thaler, Christian; Lelental, Natalia; Buchfelder, Michael; Kleindienst, Andrea; Maler, Juan Manuel; Kornhuber, Johannes; Lewczuk, Piotr (Journal of Alzheimer's Disease, 2014)
Little information is available on the rostro-caudal concentration gradient of Alzheimer's disease (AD) biomarkers.We studied the concentrations of amyloid-? (A?) peptides 1-42 and 1-40 as well as the Tau and pTau proteins in simultaneously collected ventricular and lumbar cerebrospinal fluid (CSF) samples.The samples were simultaneously collected from the ventricle and the lumbar spinal canal in two groups of patients: 10 subjects being treated for normal pressure hydrocephalus (NPH) by the placement of a ventriculo-peritoneal shunt and 5 patients treated simultaneously with an external ventricular drain and a lumbar CSF drain due to posttraumatic hydrocephalus (PTH).The ventricular-lumbar (V/L) concentration ratio for A?1-40 was 0.81 in NPH patients and 0.71 in PTH patients. The V/L-ratio for A?1-42 was 0.84 in NPH, reflecting significantly higher concentrations in lumbar CSF than in ventricular CSF, and 1.02 in PTH patients. The V/L-ratios for Tau and pTau differed significantly depending on the diagnostic group: the median V/L-ratio for Tau was 6.83 in NPH patients but only 0.97 in PTH patients. The median V/L-ratio for pTau was 2.36 in NPH patients and 0.91 in PTH patients.We conclude that the rostro-caudal concentration gradient for brain-derived proteins (Tau and pTau in this study) depends on the diagnosis and clinical status of the patient, which were largely neglected in the previously postulated models.
EVALuna2:22827